High thermoelectric performance from high carrier mobility and reduced lattice thermal conductivity in Ba, Yb double-filled Skutterudites. (March 2019) - Qin, D.; Cui, B.; Meng, X.; Qin, P.; Xie, L.; Zhang, Q.; Liu, W.; Cao, J.; Cai, W.; Sui, J.
Abstract: The semicoherent low-angle grain boundaries with dense dislocation arrays have been confirmed as an effective way to improve the thermoelectric properties for Yb single-filled Skutterudites using liquid-phase compaction method in our previous work. It is known that fillers with different rattling frequencies can scatter a wider spectrum of phonons, leading to further reduced lattice thermal conductivity. Thus, on the basis of liquid-phase compaction method, Ba, Yb double-filled Skutterudites were successfully synthesized. Ba, Yb double filling and liquid-phase compaction method synergistically optimize carrier concentration and reduce lattice thermal conductivity, resulting in exceptional high PF of 57 μW cm −1 K −2 at 773 K and excellent thermoelectric figure of merit ZT = 1.53 at 823 K. Correspondingly, the high theoretical output power density ∼15.6 W cm −2 and leg efficiency ≈14% can be obtained by calculation assuming the leg length of 2 mm, hot-side temperature T h = 800 K, and cold-side temperature T c = 300 K. This work highlights that the obtained Skutterudites display great promise for harvesting electricity from waste heat with heat source at the medium temperature range. Graphical abstract: We intentionally introduce Ba, Yb fillers (notable difference in atom mass and ionic radius) and dense dislocation arrays via liquid phase compaction method to synergistically optimize carrier concentration and further reduce lattice thermal conductivity. Ba0.15 Yb0.3 Co4 Sb12 + 20% Sb exhibits exceptional high PF of 57 μW cm −1 K −2 at 773 K and excellent thermoelectric figure of merit ZT = 1.53 at 823 K. More remarkable output power density ≈15.6 W cm −2 and leg efficiency ≈14% are obtained under the conditions of T c = 300 K, T h = 800 K, and L = 2 mm. The output power density is highest among the filled Skutterudites, and efficiency is comparable with the state-of-the-art filled Skutterudites under the same conditions.Image 1 Highlights: Ba, Yb fillers and dislocation arrays are induced via liquid-phase compaction. The highest PF = 57 μW cm −1 K −2 is obtained for excellent carrier mobility. The lattice thermal conductivity is further suppressed because of double filling. Ba0.15 Yb0.3 Co4 Sb12 + 20%Sb sample exhibits the highest ZT = 1.53 at 823 K. The output power density and efficiency are outstanding among the filled CoSb3 .